2007
DOI: 10.2337/dc06-2000
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Outpatient Prescription Drug Costs in Diabetic Patients in Germany, 1994–2004

Abstract: OBJECTIVE -New antidiabetic medications have been introduced during the last decade, but their impact on health care cost is largely unknown. Prescription costs in diabetic patients in primary care in Germany were evaluated (1994 -2004).RESEARCH DESIGN AND METHODS -A total of 46,017 diabetic patients and 46,017 age-and sex-matched control subjects in 400 nationwide practices (2004) were compared with 29,956 diabetic patients and 13,226 control subjects (361 practices) in 1994 (data from IMS HEALTH). Inflation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
26
1
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 20 publications
3
26
1
1
Order By: Relevance
“…However, metformin has only been licensed by the US FDA since 1995 [6]. A decrease in the prescribing of sulphonylureas and an increase in the prescribing of metformin have also been observed in Germany, Italy and Japan [7][8][9][10].…”
Section: Date Submitted 1 November 2013; Date Of First Decision 2 Janmentioning
confidence: 99%
See 1 more Smart Citation
“…However, metformin has only been licensed by the US FDA since 1995 [6]. A decrease in the prescribing of sulphonylureas and an increase in the prescribing of metformin have also been observed in Germany, Italy and Japan [7][8][9][10].…”
Section: Date Submitted 1 November 2013; Date Of First Decision 2 Janmentioning
confidence: 99%
“…However, metformin has only been licensed by the US FDA since 1995 [6]. A decrease in the prescribing of sulphonylureas and an increase in the prescribing of metformin have also been observed in Germany, Italy and Japan [7][8][9][10].Since the publication of the results from the University Group Diabetes Programme (UGDP) in 1969, there has been controversy surrounding the use of sulphonylureas to lower blood glucose in people with type 2 diabetes. In this large, multicentre, placebo-controlled trial, patients were randomized to placebo plus diet, fixed-dose tolbutamide (a first-generation sulphonylurea), fixed-dose insulin or a variable dose of insulin dependent on fasting plasma glucose.…”
mentioning
confidence: 99%
“…Several studies have targeted the prescription of antihyperglycemic drugs and the cost of these medications in Germany. [9][10] In 2007, Rathmann and colleagues discovered that there had been a 100% increase in the average cost for antidiabetic medication between 1994 (€86.7) and 2004 (€172.1). 9 More recently, Tamayo et al further found regional and individual social disparities in the cost of overall and newer antihyperglycemic medications unexplained by other confounders.…”
Section: Original Articlementioning
confidence: 99%
“…It is therefore not surprising that health care costs more than double after the diagnosis of diabetes is made, although it may be more unexpected that per capita costs are greater in type 2 diabetics and that hospitalizations account for more than 70% of these costs [5]. In the last 10 years, prescription costs for diabetics increased by more than 50% [6].…”
Section: Introductionmentioning
confidence: 99%